The Impact Of Artificial Intelligence On Economic Productivity - Zeghdi, Adel (جامعة الوادي University of Eloued, 2025)
In my This paper, I explore the impact of artificial intelligence (AI) on economic productivity through a comprehensive sectoral analysis. As AI technology continues to revolutionize traditional business models, I argue that it significantly enhances productivity across various sectors by automating tasks, optimizing processes, and facilitating data-driven decision-making. My findings are structured into three main sections: the definition and evolution of AI in industry, an analysis of productivity impacts from multiple perspectives, and sector-specific case studies showcasing real-world applications. Each section supports in this paper, demonstrating AI's transformative role in driving efficiency and contributing to economic growth. The conclusion emphasizes AI's potential to reshape industry landscapes while highlighting the need for responsible innovation to address potential challenges, such as employment and economic inequality.
The Impact of Artificial Intelligence on Economic Productivity A Sectoral Analysis
مقال
Keywords: Artificial Intelligence; Economic Productivity; Automation; Sectoral Analysis; Innovation.